2013
DOI: 10.4236/as.2013.412087
|View full text |Cite
|
Sign up to set email alerts
|

Response of cranberry and kidney beans to linuron

Abstract: ABSTRACT. One week after emergence (WAE), linuron applied PRE caused 0.4% to 1.2% injury in "Etna", "Hooter", "SVM Tayler", and "Capri" cranberry bean and 3.1% to 3.6% injury in "Red Hawk", "Pink Panther", "Calmont", and "Majesty" kidney bean. At 2 and 4 WAE, there was no difference in injury among the dry bean cultivars. Contrast comparing injury due to linuron in cranberry vs kidney bean cultivars indicated 2.3%, 1.7%, and 1.2% greater injury in kidney bean compared to cranberry bean at 1, 2, and 4 WAE, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…ha −1 did not have any adverse effect on the yield of cranberry and kidney bean [22]. In another study, linuron applied PRE at various doses did not cause any adverse effect on the yield of cranberry, kidney and white beans but yield of black bean was reduced 16% compared to the non-treated control at 2500 g•ha −1 [17]. Other studies have also shown that imazethapyr and s-metolachlor applied alone or in combination with other herbicides cause no reduction in yield of dry bean [3] [6] [18]- [21].…”
Section: Crop Injury and Yieldmentioning
confidence: 92%
See 1 more Smart Citation
“…ha −1 did not have any adverse effect on the yield of cranberry and kidney bean [22]. In another study, linuron applied PRE at various doses did not cause any adverse effect on the yield of cranberry, kidney and white beans but yield of black bean was reduced 16% compared to the non-treated control at 2500 g•ha −1 [17]. Other studies have also shown that imazethapyr and s-metolachlor applied alone or in combination with other herbicides cause no reduction in yield of dry bean [3] [6] [18]- [21].…”
Section: Crop Injury and Yieldmentioning
confidence: 92%
“…These results are similar to other studies that have shown less than 4% injury in kidney bean with linuron applied applied PRE at 1125 and 2250 g a.i. ha −1 [17]. Similarly, imazethapyr and s-metolachlor applied alone or in combination with other herbicides have been shown to cause minimal injury in dry bean with soil applied PRE herbicides including imazethapyr and s-metolachlor [3] [6] [18]- [21].…”
Section: Crop Injury and Yieldmentioning
confidence: 99%